Hubungan Pola Asuh Orang Tua dengan Motivasi Belajar Siswa Kelas 4 SD Negeri 064027 Medan Polonia - Anis Fitria Harahap (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to find a significant relationship between parental care in class IV of SD Negeri 064072 Medan Polonia and their motivation to study with the research title "The Relationship between Parenting Patterns and the Learning Motivation of Class 4 Students of SD Negeri 064027 Medan Polonia T.A 2023/ 2024”. The data collection technique or instrument used is a questionnaire whose validity and reliability are tested. The sample in this study was 30 grade IV elementary school students. The data analysis techniques used are normality test, homogeneity test, relationship coefficient test, and hypothesis test. The research results showed that the correlation coefficient data calculation obtained a correlation interpretation value of 0.985. The value of 0.985 is located between the coefficients 0.80-1.00. So it can be concluded that: 1) the magnitude of the correlation coefficient between the independent variable Parenting Patterns (X) and the dependent variable learning motivation (Y) SD Negeri 064027 Medan Polonia T.A 2023/2-24 is classified at a very high level. 2) The normality test obtained an average value of 87.003. Based on the calculations, it is found that Lcount = 0.14133 and Ltabel = 0.161 with a significance level of α = 0.05, so Lcount < Ltabel (0.14133 < 0.161) which means the Ho hypothesis is accepted. So it can be concluded that the data is normally distributed. 3) From a level of 28, the ttable obtained at a 5% significance level is 2.001717468. So it is concluded that there is a positive relationship between parenting patterns and the learning motivation of class IV students at SD Negeri 064027 Medan Polonia for the 2023/2024 academic year.